1985
DOI: 10.1126/science.230.4727.822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fibrils in Vitro by a Solubilized Cellulose Synthase from Acetobacter xylinum

Abstract: A digitonin-solubilized cellulose synthase was prepared from Acetobacter xylinum. When this enzyme was incubated under conditions known to lead to active synthesis of 1,4-beta-D-glucan polymer (cellulose), electron microscopy revealed that clusters of fibrils were assembled within minutes. Individual fibrils are 17 +/- 2 angstroms in diameter. Evidence that the fibrils were freshly synthesized and cellulosic in nature was their incorporation of the tritium from UDP-[(3)H]glucose (UDP, uridine 5'-diphosphate), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…There are three possibilities for the decreased number of cellulose molecules in the brittle cell walls: (a) involvement of a brittle gene in the number of cellulose-forming complexes. Itoh et al (13) reported that the estimated number ofterminal complexes is nearly similar to the estimated number ofglucan chains within the microfibrils; (b) impediment in the assembly process of cellulose-forming complexes; and (c) decrease in UDP-Glc precursor in cellulose synthesis (8,16).…”
Section: Discussionmentioning
confidence: 99%
“…There are three possibilities for the decreased number of cellulose molecules in the brittle cell walls: (a) involvement of a brittle gene in the number of cellulose-forming complexes. Itoh et al (13) reported that the estimated number ofterminal complexes is nearly similar to the estimated number ofglucan chains within the microfibrils; (b) impediment in the assembly process of cellulose-forming complexes; and (c) decrease in UDP-Glc precursor in cellulose synthesis (8,16).…”
Section: Discussionmentioning
confidence: 99%
“…The most reliable methods to prove the presence of crystalline cellulose are x-ray and electron diffraction analyses (Lin et al, 1985;Bureau and Brown, 1987). Highly purified cellulase conjugated to colloidal gold has been used as a probe to identify cellulose by TEM (Lin et al, 1985).Cotton (Gossypium hirsutum) fiber cells have been used by many investigators for the study of cellulose biosynthesis (Delmer et al, 1984;Buchala and Meier, 1985). Experiments in which intact fibers from cotton fruit capsules (Pillonel and Meier, 1985), intact fibers from ovule cultures (Francey et al, 1989), and anucleate protoplasts isolated from fiber cells (Gould et al, 1986) were used have demonstrated cellulose synthesis.…”
mentioning
confidence: 99%
“…The AN reagent (Updegraff, 1969) has been used for the selection of cellulose because only crystalline cellulose can remain after treatment with this reagent. The most reliable methods to prove the presence of crystalline cellulose are x-ray and electron diffraction analyses (Lin et al, 1985;Bureau and Brown, 1987). Highly purified cellulase conjugated to colloidal gold has been used as a probe to identify cellulose by TEM (Lin et al, 1985).…”
mentioning
confidence: 99%
“…The in vitro product derived from digitoninsolubilized membranes has been suggested to occur as fibrils 17 ± 2 A in diameter having an electron diffraction pattern similar to cellulose I (13).…”
mentioning
confidence: 99%